High Prevalence of Myotonic Dystrophy Type I in a Town of Colombia - Bendeck, Joanna L.; Jeimy Forero; Sharon Lechtig; María Paula Prieto; Oriana Lujan; Natalia Gómez; Carolina Prieto; Daniela Polania; María Ximena Arteaga; Alexandra Arias; Mariana Castellanos; Carolina Torres; et al. (Journal of Medical Biomedical and Applied Sciences, 2021)
Check full pdf